Securing the Internet of Things – part one. Issue 12 (December 2018) - Unknown
Abstract : Computers have crept into every corner of our lives. At home, they are embedded in TVs, routers, webcams, baby monitors and even toys. At work, computers are no longer confined to the office – they are deeply integrated into the machines that run our water and energy systems, control traffic of all kinds, manufacture goods and materials, and much more.